2004
DOI: 10.1007/s00253-003-1498-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-conventional yeasts as producers of polyhydroxyalkanoates?genetic engineering of Arxula adeninivorans

Abstract: The non-conventional yeast Arxula adeninivorans was equipped with the genes phbA, phbB and phbC of the polyhydroxyalkanoate (PHA) biosynthetic pathway of Ralstonia eutropha, which encode beta-ketothiolase, NADPH-linked acetoacetyl-CoA reductase and PHA synthase, respectively. Arxula strains transformed solely with the PHA synthase gene (phbC) were able to produce PHA. However, the maximum content of the polymer detected in these strains was just 0.003% poly-3-hydroxybutyrate (PHB) and 0.112% poly-3-hydroxyvale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…It is known that the Nile-red stain emitted strongly positive red fluorescence signals only with hydrophobic compounds like PHAs and lipids. Nile-red intended to show any lipid particles inside the cells and it did not react with any tissue constituent except by solution and could be detected by fluorescence spectroscopy or flow cytometery (Terentiev, et al, 2004). The results of the Nile-Red staining assay were compatible with both restriction mapping and the PCR detection assays of PHB genes.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…It is known that the Nile-red stain emitted strongly positive red fluorescence signals only with hydrophobic compounds like PHAs and lipids. Nile-red intended to show any lipid particles inside the cells and it did not react with any tissue constituent except by solution and could be detected by fluorescence spectroscopy or flow cytometery (Terentiev, et al, 2004). The results of the Nile-Red staining assay were compatible with both restriction mapping and the PCR detection assays of PHB genes.…”
Section: Discussionmentioning
confidence: 65%
“…Previously, Leaf et al, (1996), Breuer, et al, (2002 and Terentiev et al, (2004) reported that no increase in PHA levels produced by expressing the entire threegene PHA pathway compared with those found in yeast transformants where only the phbC gene was expressed. They suggested that competition for the precursors from pathways may lead to the synthesis of other storage compounds.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…An expression platform based on A. adeninivorans has been developed in recent years, and has been used to synthesize recombinant proteins such as human serum albumin (HSA), lipase, invertase, xylitol dehydrogenase, transaldolase, interleukin-6, α-amylase, acid phosphatase and phytase, and for production of polyhydroxyalkanoates (Wartmann et al, 2002(Wartmann et al, , 2003a(Wartmann et al, , 2003bBöer et al, 2004bBöer et al, , 2005aBöer et al, , 2005bBöer et al, , 2005cBöer et al, , 2007Terentiev et al, 2004;Steinborn et al, 2005Steinborn et al, , 2007El Fiki et al, 2007;Kaur et al, 2007). The system involves the use of vectors with multiple cloning sites for the integration of selection markers, expression cassettes bearing strong constitutive or inducible promoters, autonomously replicating sequences and chaperone cassettes, which are inserted between rDNA-targeting sequences (Steinborn et al, 2007).…”
Section: E Böer Et Almentioning
confidence: 99%